Balap Kata Board Game: Revitalizing Traditional Scripts for National Awareness - Filashofia, Etika; Usman, Muhammad Jalaluddin (Jurnal Bisnis dan Pemasaran Digital, 2025)
Purpose: Balap Kata is an educational innovation designed to promote national values and foster awareness of local identity among younger generations amid modernization. Methodology/approach: This study employs a qualitative-descriptive approach, combining literature review and conceptual analysis to examine the game as a learning medium. The discussion includes game design, mechanics, conveyed cultural values, and relevance in shaping national awareness. Results/findings: Balap Kata is a board game centered on arranging Javanese vocabulary using two scripts: Aksara Jawa and Arab Pegon. Aksara Jawa consists of 20 basic characters, known as Aksara Nglegena, while Arab Pegon adapts Arabic letters (Hijaiyah) for Javanese writing. Both represent the Javanese linguistic heritage, functioning as tools of communication and knowledge preservation that embody the philosophical and spiritual depth of Javanese culture. Conclutions: The study shows that Balap Kata has significant potential as an educational tool to revive interest in regional languages and strengthen national identity through linguistic heritage. Limitations: The focus on Aksara Jawa and Arab Pegon highlights their symbolic role in the forgotten cultural and spiritual synthesis of Javanese civilization. Contribution: Revitalizing traditional scripts through such games supports character education based on local culture.